Elasticities of Demand for U.S. Exports: A Reply - Adler, Michael (The Review of Economics and Statistics, 1971)
[1] Adler, F. M., The Relationship between the and Price Elasticities of Demand for United States Exports, this REVIEW, LII (Aug. 1970), pp. 313-319. [2] Banca D'Italia, Elasticita di domanda e di prezzo nel cominercio estero dei principali paesi industriali, Rome, 1970. Salvatore Leonetti is the author. An abridged version appeared in the Bank of Italy's Bolletino, XXV (Jan.-Feb. 1970). [3] Houthakker, H. S. and S. P. Magee, Income and Price Elasticities in World Trade, this REVIEW, LI (May 1969), pp. 111-125. [4] Office of Statistics and Reports, Agency for International Development, Gross National Product: Growth Rates and Trend Data by Region and by Country (April 30, 1970), RC-W-138.